"I've had a magical journey": understanding how international sports coaches learn through cross-sport boundary encounters. Issue 2 (4th May 2021) - Vinson, Don; Huckle, Victoria; Cale, Andrew
ABSTRACT: Recent approaches to facilitating coach development place considerable emphasis on social interaction aimed at enhancing participants' learning through collaboration and discussion. This investigation examined the usefulness of utilising the Landscapes of Practice (LoP) framework to better understand such "social" learning, specifically focussing on boundary interactions experienced by international coaches. Having recently undertaken a cross-sport development programme, 14 coaches from 11 sports were interviewed and a thematic structure was subsequently established featuring four categories: (a) confidence, openness and authenticity, (b) sense making, (c) reflection and mentoring and (d) reconceptualising and reframing. This investigation found strong support for the usefulness of the LoP framework. Furthermore, knowledgeability and boundary interactions were insightful concepts to better understand how coaches learnt through interactions within, and beyond, the programme. For example, cross-sport interactions enabled some coaches to learn more effectively because they felt less encumbered by peers' judgements when compared to other environments.